2016
DOI: 10.1080/19476337.2016.1162847
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activities of Bidens pilosa and Moringa oleifera leaf extracts and their effects on ground beef quality during cold storage

Abstract: This study determined the activities of Bidens pilosa and Moringa oleifera leaf extracts on microbial count of ground beef during 6-day cold storage. Fresh ground beef sample was treated with butylated hydroxytoluene (BHT) (0.2 g/kg), M. oleifera (ML, 1 g/kg) and B. pilosa (BP, 1 g/kg) leaf extracts and compared with the control. The result of the phytochemical contents revealed that ML extract had higher phenolic and flavonoid contents than BP extract (p > 0.05). The antibacterial assay of the extracts reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
4
24
2
1
Order By: Relevance
“…Moringa leaf powder contains high levels of flavonoids, vitamin E, A and selenium, which could have contributed to the observed high antioxidant activity in the current study synergistically, as reported elsewhere (Falowo et al, 2016). Babiker et al (2017) and Gopalakrishnam et al (2016) reported that positive Moringa effects on milk yield were associated with a higher intake of the plant.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moringa leaf powder contains high levels of flavonoids, vitamin E, A and selenium, which could have contributed to the observed high antioxidant activity in the current study synergistically, as reported elsewhere (Falowo et al, 2016). Babiker et al (2017) and Gopalakrishnam et al (2016) reported that positive Moringa effects on milk yield were associated with a higher intake of the plant.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, M. oleifera leaf meal contains phenolic and flavonoids at 31.9 g/100g and 40.8 g/100g, respectively (Pakade et al, 2013). These compounds have antioxidative and immunomodulatory properties (Moyo, 2011) that are more effective than synthetic antioxidants such as butylated hydroxytoluene, rutin, and ascorbic acid as noted by Falowo et al, (2016). Because early lactating dairy cows are prone to oxidative stress, M. oleifera may serve as a natural and cheaper antioxidant source in resource limited-areas.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in the current reaserch, the T. trifidum extracts showed activity against gram-negative and gram-positive bacteria. A related study, but using extracts from Bidens pilosa and Moringa oleifera ( Falowo et al., 2016 ), also showed potency against gram-negative bacteria. It is noteworthy that like the T. trifidum extracts, the B. pilosa and M. oleifera extracts, also contained phytochemicals with antibacterial activity.…”
Section: Discussionmentioning
confidence: 91%
“…The dried powder of plant extracts were then stored at 20°C for further analysis. The phenolic contents of the extracts have been analyzed previously (Falowo et al, 2016).…”
Section: Plant Sample and Extract Preparationmentioning
confidence: 99%
“…Reports on their nutritional contents have also showed that they are rich in proteins (including essential amino acids), vitamins, beta-carotene, minerals and low in fat and carbohydrates (Adedapo et al, 2011;Moyo et al, 2012;Bartolome et al, 2013). The antioxidant and biological activities of these plants have been attributed to the presence of phytochemicals including flavonoids and other phenolics in their leaves extract (Al-Owaisi, Al-Hadiwi, & Khan, 2014;Falowo, Muchenje, Hugo, & Charimba, 2016).…”
Section: Introductionmentioning
confidence: 99%